2023
DOI: 10.1186/s13054-023-04555-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous renal replacement therapy with the adsorptive oXiris filter may be associated with the lower 28-day mortality in sepsis: a systematic review and meta-analysis

Abstract: Background The oXiris is a novel filter for continuous renal replacement therapy (CRRT) featuring an adsorption coating to adsorb endotoxins and remove inflammatory mediators. Given that no consensus has been reached on its potential benefits in treating sepsis, a meta-analysis was conducted to assess its impact on the clinical outcomes of this patient population. Methods Eleven databases were retrieved to find relevant observational studies and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…3 A&B&C).These findings are in line with other reported cases [ 17 , 18 , 20 ]. Recent meta-analysis shows oXiris reduces sepsis 28-day mortality, ICU days, improves SOFA scores, lowers norepinephrine, IL-6, and lactate [ 28 , 29 ]. This aligns with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…3 A&B&C).These findings are in line with other reported cases [ 17 , 18 , 20 ]. Recent meta-analysis shows oXiris reduces sepsis 28-day mortality, ICU days, improves SOFA scores, lowers norepinephrine, IL-6, and lactate [ 28 , 29 ]. This aligns with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, which compiled clinical data from 10 cohort studies and 4 RCTs encompassing 695 patients with sepsis undergoing CRRT, suggested potentially positive effects on 7-, 14-, and 28-day mortality, SOFA score, catecholamine requirement, lactate level, and length of ICU stay [ 43 ]. However, the quality of the studies included was not sufficient to draw definitive conclusions.…”
Section: Combination Methodsmentioning
confidence: 99%
“…It is worth noting that the primary result from Wang et al [ 1 ] heavily relies on retrospective studies, raising concerns about the possibility of publication bias, as negative results from retrospective cohort studies might not have been published. Additionally, half of the enrolled studies (7 out of 14 enrolled trials) did not report the 28-day mortality outcome.…”
Section: Limited Meta-analysismentioning
confidence: 99%
“…It is highly encouraged to validate the impact of oXiris using evidence-based medicine methodologies. We carefully reviewed the recently published systematic review by Wang et al [ 1 ] and found it to be highly intriguing. A significant reduction with a substantial effect in 28-day mortality (odds ratio [OR] 0.53; 95% confidence interval [CI] 0.36–0.77, I 2 = 8%), which is considered one of the critical endpoints, was observed through meta-analysis using data from 7 out of 14 enrolled studies.…”
mentioning
confidence: 99%